2024
DOI: 10.3390/nano14020160
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Nanoparticles in Protecting the Brain from Stroke: Possible Signaling and Metabolic Mechanisms

Egor A. Turovsky,
Alexey S. Baryshev,
Egor Y. Plotnikov

Abstract: Strokes rank as the second most common cause of mortality and disability in the human population across the world. Currently, available methods of treating or preventing strokes have significant limitations, primarily the need to use high doses of drugs due to the presence of the blood–brain barrier. In the last decade, increasing attention has been paid to the capabilities of nanotechnology. However, the vast majority of research in this area is focused on the mechanisms of anticancer and antiviral effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 191 publications
0
1
0
Order By: Relevance
“…In a comprehensive experimental exploration, Alim et al [29] demonstrated that brain-permeable selenopeptide supplementation improves neurological function in stroke by coordinating the activation of the transcription factors TFAP2c and Sp1 to protect neurons, thereby enhancing glutathione peroxidase 4 (GPX4) and other genes, and thereby inhibiting GPX4-dependent ferroptosis and other GPX4-independent cell death. Additional experimental studies have similarly shown that selenium supplementation ameliorates oxidative stress, iron death, metabolic, and in ammatory signaling pathways in mouse ischemic stroke models [30][31][32][33].…”
Section: Discussionmentioning
confidence: 94%
“…In a comprehensive experimental exploration, Alim et al [29] demonstrated that brain-permeable selenopeptide supplementation improves neurological function in stroke by coordinating the activation of the transcription factors TFAP2c and Sp1 to protect neurons, thereby enhancing glutathione peroxidase 4 (GPX4) and other genes, and thereby inhibiting GPX4-dependent ferroptosis and other GPX4-independent cell death. Additional experimental studies have similarly shown that selenium supplementation ameliorates oxidative stress, iron death, metabolic, and in ammatory signaling pathways in mouse ischemic stroke models [30][31][32][33].…”
Section: Discussionmentioning
confidence: 94%